Heavy Metal Screening in Compounds Feeds - Tomas Toth; Michal Arva; Miriama Kopernicka; Marek Slavik; Jan Tomas; Peter Lazor; Judita Bystricka; Petra Kavalcova (Scientific Papers Animal Science and Biotechnologies, 2023)
Heavy metals are generally classified as basic groups of pollutants that are nowadays found in different environmental compartments. This is quite a large group of contaminants, which have different characteristics, effects on the environment and sources of origin. For environment pose the greatest risks, especially heavy metals produced by anthropogenic activities that adversely affect the health and vitality of organisms and natural environmental conditions. Livestock nutrition is among the main factors which affect not only the deficiency of livestock production and quality of food of animal origin, but they are also a factor affecting the safety and wholesomeness and the animal health. Compound feeds is characterized as a mixture of two or more feed grain. Containing organic, inorganic nutrients and specifically active compound feed meet the nutritional requirements of a given kind and age category of animals. They are used mainly in the diet of pigs, poultry, but also the nutrition of cattle, sheep, horses and other animal categories. The basic ingredients are cereals in proportion of 60-70 %. The aim of this thesis was to analyze the content of hazardous elements (copper, zinc, iron, manganese, cobalt, nickel, chromium, lead, cadmium, mercury) in 15 samples of compound feeds and then evaluating their content in comparison with maximum limits laid down by Regulation of the Government of the Slovak Republic and Regulation Commission (EC).